“SISTERHOOD” DI DALAM NOVEL A THOUSAND SPLENDID SUNS KARYA KHALED HOSSAENI - Adeline Grace; Tri Pramesti (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2022)
This paper aims to describe the friendship of two women from two different generations in Afghanistan from the Soviet takeover in the 1980s until after 9/11. The Life of an Afghan Woman is depicted through two female characters who try to live a normal and peaceful life as anyone in the world wants. Dominated by a strong patriarchal culture in society and a life journey full of twists and turns, the characters of Mariam and Laila are strong women who face all kinds of suffering. Using feminist literary approach, the novel is scrutinized by applying close reading method. This research is a descriptive qualitative. Based on the analysis, the inferior position of women is a result of male domination in all aspects of life. It is concluded that women are oppressed economically, traditionally and ideologically. The oppression of women makes them have strong bonds and support each other to fight oppression by men.